Epidemiology and antibiotic susceptibility profiles of obligate anaerobes in a hospital of central Italy during a one-year (2019) survey. (December 2022) - Parisio, Eva Maria; Camarlinghi, Giulio; Antonelli, Alberto; Coppi, Marco; Mosconi, Lara; Rossolini, Gian Maria
Abstract: Objectives: In this study, we report on the epidemiology and susceptibility profiles of anaerobic pathogens consecutively isolated from various clinical samples at an Italian hospital during a one-year survey. Methods: The collection included all non-duplicated consecutively collected anaerobic clinical isolates during 2019 in San Luca Hospital (Lucca, Italy). Antimicrobial susceptibility testing was performed using MICRONAUT-S Anaerobes MIC lyophilized plates (MERLIN Diagnostika, Germany) and interpreted using EUCAST criteria (11.0). Results: A total of 169 Gram-negative and 213 Gram-positive were collected. The most frequent anaerobes were Bacteroides spp. (120, 31.4%) followed by Finegoldia magna (62, 16.2%). External ulcers were the most common source of isolates (39%), followed by blood (25.7%). In 230 patients (65%) polymicrobial aerobic/anaerobic isolates were cultured from the same external ulcer specimen. High resistance rates to clindamycin were overall detected, with the highest values among the genera Parabacteroides, Bacteroides, Prevotella, Gram-positive anaerobic cocci and Clostridium . High resistance rates were also observed to metronidazole among both Gram-positive and Gram-negative species, ranging between 10.8-50% and 13.8–46.2%, respectively. Conclusions: Our findings revealed that anaerobes susceptibility patterns have become less predictable due to an increase of resistance and suggest that periodic resistance surveillance should also be carried out for anaerobes in order to guide empirical therapy. Highlights: The most common anaerobes from clinical specimens are Bacteroides and Finegoldia . External ulcers are the most common source of anaerobic bacteria infections. High resistance rates to clindamycin and metronidazole among anaerobic bacteria. Anaerobes antimicrobial susceptibilities are changing and not easily predictable.